Mathematics Teacher Education Training for Quality School Teachers: An Assessment of Mathematics Teaching Needs of Preservice Teachers’ - Alhaji, Ibrahim Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the results of assessment of preservice mathematics teachers’ teaching needs study, conducted with university mathematics teacher education training final year preservice teachers who were preparing to become secondary school mathematics teachers and undergo teaching practice exercise, and teaches mathematics at various secondary schools. The semi structure interview assessed preservice teachers’ perspectives on their teaching needs, based on the experience and difficulties encountered during teaching practice. The qualitative results revealed that teaching practice experiences was interested and memorable event that provide preservice teachers with a lot of learning opportunities and gave them confidence to teach mathematics after graduation. The finding also revealed that there is disconnection between the training curriculum contents and school mathematics curriculum for which preservice teachers were being train to teach. A conclusion and suggestion on how the training should be run, and contents areas if included the quality of preservice teachers would be improve were discussed.